Postpartum profiling of microRNAs involved in pathogenesis of cardiovascular/cerebrovascular diseases in women exposed to pregnancy-related complications - Hromadnikova, Ilona; Kotlabova, Katerina; Dvorakova, Lenka; Krofta, Ladislav (International journal of cardiology, 2019)
BACKGROUND AND METHODS: Gestational hypertension (GH), preeclampsia (PE) and fetal growth restriction (FGR) may predispose to later onset of cardiovascular/cerebrovascular diseases. We examined if pregnancy complications induce postpartum alterations in gene expression of cardiovascular/cerebrovascular disease associated microRNAs. 29 microRNAs were tested in peripheral blood of women, compared between groups with a history of GH, PE, FGR and controls, and correlated with the severity of the disease regarding clinical signs, delivery date, and Doppler parameters. RESULTS: GH was associated with the up-regulation of miR-20a-5p, miR-143-3p, miR-146a-5p, miR-181a-5p, miR-199a-5p, miR-221-3p, and miR-499a-5p. The up-regulation of miR-17-5p, miR-20b-5p, miR-29a-3p, and miR-126-3p was a mutual phenomenon of GH and severe PE. GH and early PE were associated with up-regulation of miR-1-3p and miR-17-5p. GH and late PE showed up-regulation of miR-17-5p, miR-20b-5p, and miR-29a-3p. Severe PE induced up-regulation of miR-133a-3p and down-regulation of miR-130b-3p. MiR-133a-3p up-regulation was also observed in early PE. PE and/or FGR with abnormal Doppler parameters demonstrated up-regulation of miR-100-5p, miR-125b-5p, miR-133a-3p, and miR-145-5p. The combination screening was superior over using individual microRNAs for patients with GH, PE regardless of the severity of the disease, severe PE and early PE. A cardiovascular risk at patients with late PE, PE and/or FGR with abnormal Doppler parameters was identified more accurately using the single microRNA only. CONCLUSION: Epigenetic changes characteristic for cardiovascular/cerebrovascular diseases are present in women with a prior exposure to pregnancy complications. Screening of microRNAs may be used to identify patients at a higher risk of later development of cardiovascular/cerebrovascular diseases.
Keywords: genetický profil; Cerebrovascular Disorders; Pregnancy complications; poporodní období; těhotenství; Postpartum Period; Genetic Profile; Cohort Studies; mikro RNA; Middle Aged; Prevention; MicroRNA; Prospective Studies; Adult; kohortové studie; Fetal Growth Retardation; Follow-Up Studies; MicroRNAs; následné studie; Cardiovascular Diseases; ženské pohlaví; Humans; prospektivní studie; Pregnancy; kardiovaskulární nemoci; Screening; cerebrovaskulární poruchy; pilotní projekty; lidé středního věku; Risk; hypertenze indukovaná těhotenstvím; Pilot Projects; Hypertension, Pregnancy-Induced; dospělí; Female; Cardiovascular/cerebrovascular diseases; Pre-Eclampsia; preeklampsie; lidé; růstová retardace plodu